2008
DOI: 10.2319/081707-384.1
|View full text |Cite
|
Sign up to set email alerts
|

Taurodontism and Van der Woude Syndrome

Abstract: Objective: To report the occurrence of taurodontism in a clinical sample of Van der Woude syndrome (VWS) and describe its association with hypodontia and cleft type. Materials and Methods: This retrospective, cross-sectional study was carried out on chart reviews and radiographs of 13 persons with VWS. Mean age was 10 years 11 months Ϯ 1 year 5 months. Panoramic radiographs were used to confirm the presence or absence of teeth and to measure crown body and root lengths of mandibular first molars. Three-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
0
20
0
3
Order By: Relevance
“…Taurodontism appears most frequently as an isolated anomaly, but it has also been associated with several developmental syndromes and anomalies including amelogenesis imperfecta, Down's syndrome, ectodermal dysplasia, Klinefelter syndrome, tricho-dento-osseous syndrome, Mohr syndrome, Wolf-Hirschhorn syndrome and Lowe syndrome (10). Taurodontism has also been reported to present with other rare syndromes such as Smith-Magenis syndrome (11), Williams syndrome (12), McCune-Albright syndrome (13) and Van der Woude syndrome (14). Theories concerning the pathogenesis of taurodontic root formation are also varied: an unusual developmental pattern, a delay in the calcification of pulpal chamber, an odontoblastic deficiency, an alteration in Hertwig's epithelial root sheath (15).…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…Taurodontism appears most frequently as an isolated anomaly, but it has also been associated with several developmental syndromes and anomalies including amelogenesis imperfecta, Down's syndrome, ectodermal dysplasia, Klinefelter syndrome, tricho-dento-osseous syndrome, Mohr syndrome, Wolf-Hirschhorn syndrome and Lowe syndrome (10). Taurodontism has also been reported to present with other rare syndromes such as Smith-Magenis syndrome (11), Williams syndrome (12), McCune-Albright syndrome (13) and Van der Woude syndrome (14). Theories concerning the pathogenesis of taurodontic root formation are also varied: an unusual developmental pattern, a delay in the calcification of pulpal chamber, an odontoblastic deficiency, an alteration in Hertwig's epithelial root sheath (15).…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…[5] Taurodontism has also been reported to present with other rare syndromes such as Smith–Magenis syndrome,[6] Williams syndrome,[7] McCune–Albright syndrome[8] and Van der Woude syndrome. [9]…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Several studies had demonstrated the utility of the CBCT to evaluate similar situations as found in this study, such as impacted teeth, 15 dental displacements 16 and maxillary sinus membrane thickening. 17 Hashimoto et al 18 affirmed that through the CBCT it was possible to distinguish enamel, dentine, pulp cavity and alveolar bone with better clarity, whereas Noujeim et al 19 stated that the CBCT technique has better accuracy and diagnostic value than periapical films in the detection of periodontal bone defects.…”
Section: Discussionmentioning
confidence: 90%